Reconstruction of Constitutional Law to Realize Democracy with Integrity - Firmansyah, Rizky (Journal of Law and Humanity Studies, 2024)
The integrity of democracy is fundamentally dependent on the legal frameworks governing constitutional law. This study examines the reconstruction of constitutional law to ensure a democracy with integrity through a qualitative methodology, employing literature review (library research) to analyze legal principles, judicial independence, electoral integrity, and governance transparency. The study reviews ten scholarly articles from Google Scholar (2019-2024) to identify the key trends and challenges in democratic governance. Findings reveal that democratic backsliding, political corruption, and digital disinformation pose significant threats to modern democracies. Weak constitutional safeguards and political manipulation of legal institutions further exacerbate democratic erosion, as observed in several countries experiencing governance crises. The study highlights the necessity of strengthening constitutional mechanisms to ensure judicial independence, enforce electoral laws, and combat political corruption. Additionally, the role of digital governance in shaping democratic integrity is increasingly relevant, necessitating constitutional provisions that regulate digital misinformation while protecting freedom of expression. The research underscores that constitutional law must evolve dynamically to address emerging challenges while maintaining stability and democratic accountability. The study concludes that effective legal reforms require strong institutional frameworks, public participation, and international cooperation to safeguard democratic principles. Future research should explore comparative analyses between democratic systems, empirical case studies on constitutional reform implementation, and digital governance's role in election integrity. These insights contribute to ongoing discussions on the role of constitutional law in reinforcing democratic resilience against modern threats.